Pengaruh Dana Alokasi Khusus terhadap Indeks Pembangunan Manusia di Kabupaten Kebumen - Revita Hazna; Evi Grediani (AKUNTANSI 45, 2025)
This study aims to determine and analyze the effect of Special Allocation Funds (DAK) on the Human Development Indeks (HDI) in Kebumen Regency. The HDI is a comprehensive indicator used to measure the quality of human development in three main dimensions, namely health, education, and per capita expenditure. Local governments are encouraged to continue improving HDI achievements to create sustainable and equitable development. One of the efforts undertaken is through the optimization of DAK usage, which is sourced from the state budget, to support development priorities in the region. This study employs a quantitative approach using secondary data in the form of time series data from 2020 to 2024. Data was obtained from the Badan Pusat Statistik (BPS), the Regional Finance and Revenue Management Agency (BPKPD), and the Local Government of Kebumen District. The analysis technique used was simple linear regression using SPSS software. The results of the study indicate that DAK has a positive impact on the HDI in Kebumen Regency, with a regression coefficient value of 0,012. This suggests that an increase in DAK allocation contributes to improving the quality of human development in the region.